Collaborative Governance in The Lontong Kupang Program of The Surabaya City Government - Septian Aditya Saputra; Sri Wibawani (Publik : (Jurnal Ilmu Administrasi), 2025)
The Lontong Kupang Program is an integrated online service, a one-gate system between the Surabaya Population and Civil Registry Office, the Surabaya Religious Court, and the Surabaya Ministry of Religion. One of the services available in Lontong Kupang is the Mass Marriage Confirmation, which is part of the public service innovation. This program still requires further collaboration so that this program runs optimally. The purpose of this study was to analyze and describe in depth Collaborative Governance in the Lontong Kupang Program of the Surabaya City Government. This type of research is descriptive qualitative. Determination of informants through purposive sampling and snowball sampling. Data collection techniques are observation, interviews, and documentation. Collaborative governance is analyzed using the theory of Ansel & Gash (2008). The results of the study indicate that 1.) The initial conditions of the program begin with adequate readiness, including shared understanding, resources, and collaborative encouragement. 2.) The institutional design is quite structured with the participation of various parties and MoUs between government agencies, but there are weaknesses in the rules for collaboration with non-governmental institutions. 3.) The leadership of the head of the Surabaya City Population and Civil Registry Office has been effective in facilitating communication and coordination. 4.) The collaborative process shows positive results, although socialization and target achievement still need to be improved for more optimal results. So it can be concluded that collaborative governance in the Lontong Kupang Program has been running well, but further optimization is needed.